Adverse oxidation of CsPbI2Br perovskite during the crystallization process in an N2 glove-box. Issue 17 (9th April 2019) - Zhang, Shasha; Wu, Shaohang; Babu, B. Hari; Chen, Weitao; Chen, Rui; Huang, Yuqian; Yang, Zhichun; Zhu, Hongmei; Zhou, Jing; Chen, Wei
Abstract : During annealing, surface oxidation leads to defect formation in the crystals and attenuated photovoltaic performance. Abstract : Hybrid organic–inorganic perovskite solar cells (PSCs) have a major drawback of instability for long-term operation. Recently, all-inorganic cesium lead halide perovskites have emerged as thermally stable and efficient photovoltaic light absorbers. However, research on the fundamental crystallization behavior of these materials is still far from adequate. In this work, the surface morphology, crystal structure, chemical states and defect/trap conditions of CsPbI2 Br film with increasing annealing time have been systematically studied. We highlight a previously unnoted feature that adverse oxidation by traces of water (H2 O)/oxygen (O2 ) in the normally considered nitrogen (N2 ) atmosphere takes place during the crystal formation process of CsPbI2 Br perovskite. The oxidation leads to an evident increase in the defect density in the CsPbI2 Br film and remarkably deteriorated the performance of the corresponding PSC. We believe that this work provides good inspiration for the preparation of high-quality perovskite films and the fabrication of highly efficient inorganic PSCs.